Nano Online 2016
DOI: 10.1515/nano.11671_2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Photoconductivity Properties of Tellurium/PMMA Films

Abstract: (http://creativecommons.org/licenses/by/4.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly credited.Owing to the very brittle nature of tellurium powder, nanoscopic grains with an average size of 4.8 ± 0.8 nm were produced by dry vibration milling technique using a mixer/mill apparatus. A novel material was obtained by binding the nanosized tellurium grains with poly(methyl methacrylate) (PMMA) polymer. The morphology, elemental compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The particle size and homogeneous dispersion of the particle in the polymer matrix can also be related to peak intensities and peak areas. 25 In the 30 and 50 mg TiO 2 -added samples, the peak observed at 25° (d 101 plane of TiO 2 ) is sharp. Thus, it can be concluded that the filler grain size is low and the homogeneity is high in the 30 and 50 mg TiO 2 -added composites where severe peaks are observed compared to other composites.…”
Section: Resultsmentioning
confidence: 90%
“…The particle size and homogeneous dispersion of the particle in the polymer matrix can also be related to peak intensities and peak areas. 25 In the 30 and 50 mg TiO 2 -added samples, the peak observed at 25° (d 101 plane of TiO 2 ) is sharp. Thus, it can be concluded that the filler grain size is low and the homogeneity is high in the 30 and 50 mg TiO 2 -added composites where severe peaks are observed compared to other composites.…”
Section: Resultsmentioning
confidence: 90%